Transcription factor PU.1 represses and activates gene expression in early T cells by redirecting partner transcription factor binding - Hosokawa, Hiroyuki (Immunity, 2018)
Transcription factors normally regulate gene expression through their action at sites where they bind to DNA. However, the balance of activating and repressive functions that a transcription factor can mediate is not completely understood. Here, we showed that the transcription factor PU.1 regulated gene expression in early T cell development both by recruiting partner transcription factors to its own binding sites and by depleting them from the binding sites that they preferred when PU.1 was absent. The removal of partner factors Satb1 and Runx1 occurred primarily from sites where PU.1 itself did not bind. Genes linked to sites of partner factor ‘theft’ were enriched for genes that PU.1 represses despite lack of binding, both in a model cell line system and in normal T cell development. Thus, system-level competitive recruitment dynamics permit PU.1 to affect gene expression both through its own target sites and through action at a distance.